Reproductive performance of Sudan indigenous sheep under irrigated Gezira conditions - Suliman, A.H.; El-Amin, F.M.; Osman, A.H. (1978)
The study reports some of the reproductive traits, namely pregnancy length, ewe fertility and reproductive rate, pre-weaning survival and mortality rates of Sudan indigenous sheep under irrigated Gezira conditions.